2018
DOI: 10.21315/km2018.36.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Blood Donation Status in Malaysia: Profiling the Non-Donors, Occasional Donors and Regular Donors

Abstract: The blood shortage situation is a perennial concern in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
4
1
Order By: Relevance
“…Additionally, the majority of the respondents were Malay and Muslims. These findings were not in agreement with a study conducted in Penang, whereby the percentages of Malay and Chinese respondents were similar at 44.3% and 44.7%, respectively (15). This difference can be explained by the fact that Malays make up the majority (77.9%) of the population in Kedah (24).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Additionally, the majority of the respondents were Malay and Muslims. These findings were not in agreement with a study conducted in Penang, whereby the percentages of Malay and Chinese respondents were similar at 44.3% and 44.7%, respectively (15). This difference can be explained by the fact that Malays make up the majority (77.9%) of the population in Kedah (24).…”
Section: Discussioncontrasting
confidence: 86%
“…Studies have also shown that donors without formal education and staff in the formal sector were more likely to donate again (14). Meanwhile, other studies reported that donor status is associated with educational level, whereby tertiaryeducated donors were less likely to become regular donors (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on reports from the World Health Organization (WHO, 2022), 118.54 million blood donations are collected worldwide. The current situation in Malaysia is equivalent to only 22.5 donations for every thousand people (Ling et al, 2018). The Director General of Health Malaysia reported a 40% decrease in blood collection in 2020 compared to previous years.…”
Section: Introductionmentioning
confidence: 99%
“…Others depend on it after an accident or because they have a disease that requires blood components. According to World Health Organization, stated that in order to full filled the blood demand, 4.6% out of the population should come forward as a donor but only 2.25% who altruistically be as a donors [2].…”
Section: Introductionmentioning
confidence: 99%